2022
DOI: 10.1021/acsaem.2c00837
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Double Protection Strategy for High-Performance Spinel LiNi0.5Mn1.5O4 Cathodes

Abstract: LiNi0.5Mn1.5O4 is a promising cathode material with high-voltage and three-dimensional lithium-ion transport channels. Rapid capacity degradation due to HF corrosion has been a great challenge hindering the application of high-voltage cathode materials. Herein, a double protection strategy for high-performance LiNi0.5Mn1.5O4 cathodes has been designed using Li6.4La3Zr1.4Ta0.6O12 (LLZTO) with both high ionic conductivity and high surface basicity as the modifier of the poly­(vinylidene fluoride) (PVDF) binder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Other approaches have reported capacity decay of around 13 % after 300 cycles in comparison we obtain 6 % decay at the same number of cycles and 7-6 % for 500 cycles (Figure 4b). [41,44,46] Likewise, dQ/dV plots (Figure 4c) confirm a clear pattern of voltage plateau degradation becomes evident after 500 cycles. AMFB exhibits slightly higher reactivity during oxidation at high potentials compared to AMBB and that the plateau-like behavior is lost during cycling.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Other approaches have reported capacity decay of around 13 % after 300 cycles in comparison we obtain 6 % decay at the same number of cycles and 7-6 % for 500 cycles (Figure 4b). [41,44,46] Likewise, dQ/dV plots (Figure 4c) confirm a clear pattern of voltage plateau degradation becomes evident after 500 cycles. AMFB exhibits slightly higher reactivity during oxidation at high potentials compared to AMBB and that the plateau-like behavior is lost during cycling.…”
Section: Resultsmentioning
confidence: 52%
“…[40] The constant presence of mobile Li + in SLICPB helps mitigate polarization by concentration, providing an additional advantage; in this regard, it is important to highlight that although the beneficial impact of several binders in protective capability has been reported, no material has been reported to diminish polarization by concentration due to the SLICPBs. [41][42][43][44] At higher C-rates, the disparities between the binders are exacerbated, with a greater difference in capacity between the samples, being higher for AMBB. Furthermore, the slope of the charge curve at high potential remains significantly steeper for AMBB compared to AMFB, and the plateau separation increases as the C-rate rises (Figure 3b-d).…”
Section: Resultsmentioning
confidence: 99%
“…During the development of LiMn2O4 (LMO) electrodes, researchers found that the drawback lies in the inevitable dissolution of Mn during the cycle of lithium-ion adsorption and desorption, which can lead to serious problems such as capacity decay and poor cycling performance, among others [3,18]. To address this issue, LMO electrodes are being improved to reduce Mn dissolution, and manganese spinel can be doped with other metal cations to lower the Mn 3+ content in LMO, which will reduce Mn 2+ dissolution and enhance electrochemical performance.…”
Section: Spinel Lini 05 Mn 15 Omentioning
confidence: 99%
“…To address this issue, LMO electrodes are being improved to reduce Mn dissolution, and manganese spinel can be doped with other metal cations to lower the Mn 3+ content in LMO, which will reduce Mn 2+ dissolution and enhance electrochemical performance. Among these, the addition of Ni to LMO to create LiNi0.5Mn1.5O4 (LNMO) has demonstrated outstanding system cycling stability and a high potential to attract the interest of several researchers [1,18,19].…”
Section: Spinel Lini 05 Mn 15 Omentioning
confidence: 99%
“…Developing high voltage cathode materials is an efficient way to meet demands for high-energy-density lithium-ion batteries (LIBs), in addition to high-capacity cathode materials, such as LiNi 0.5 Mn 1.5 O 4 (4.7 V vs Li/Li + ) and LiCoPO 4 (4.8 V vs Li/Li + ). However, the limited lithium and cobalt resources may hinder their wide application. , Different from the “rocking chair” energy storage of LIBs, dual ion batteries (DIBs) store energy by anion (PF 6 – , TFSI – , AlCl 4 – , etc.)…”
Section: Introductionmentioning
confidence: 99%